PROLOG study: main results and guidance for further action - S. Yu. Martsevich; S. A. Shalnova; A. D. Deev; N. P. Kutishenko; V. V. Yakusevich (Кардиоваскулярная терапия и профилактика, 2006)
The article contains main results of PROLOG study, that compared effectiveness of controlled arterial hypertension therapy in step-wise antihypertensive treatment scheme: ACE inhibitor, spirapril, with addiction, if necessary, of diuretic hydrochlorthiazide, and beta-adrenoblocker atenolol (intervention group), vs standard treatment, prescribed by out-patient clinic doctors (control group). The follow-up period lasted for one year. Throughout the study period, systolic and diastolic blood pressure levels were significantly lower in intervention group than in control one. Cardiovascular event risk reduction was more pronounced in intervention group: 33% vs 22% in control group. PROLOG study results coincide with data from other large-scale, randomized, controlled studies.